Induction Of Ovulation Using Ovaprim And Its Impact On Reproductive Parameter Of Clarias gariepinus - Anak Gaung, Paul Morisson; Ismail, Zalina; Abdul Mutalib, Asilah; Ismail, Fazhana; Che Man, Shaibatul ’ Islamiah; Ab Latif, Zahidah (Universitas Ahmad Dahlan, 2020)
Sustainability of the aquaculture industry can be secure through the induce breeding technique. One way that induce breeding can do is to increase the rate of maturation and ovulation in making sure the availability of good quality fish seed all year round. Here, we investigate how Ovaprim hormone impact the reproduction of Clarias gariepinusincluding spawning rate, fecundity, hatching and survival rate. For this purpose, Six broodstocks were divided in three experimental treatments and injected intramuscularly with different doses of Ovaprim hormone of T1: 0.25ml/kg for female and 0.125ml/kg for male, T2: 0.5ml/kg for female and 0.25ml/kg for male and T3: 1.0ml/kg for female and 0.5ml/kg for male. According to our results, broodstock injected with Ovaprim hormone of dose of T3: 1.0ml/kg for female and 0.5ml/kg for male showed higher eggs production and hatching rate compared to other treatment. The results of this study suggest that a dosage of 1.0ml/kg Ovaprim for female and 0.5ml/kg for male have a better effect on the reproductive parameter of Clarias gariepinus.